Elaboration of a vegan short dread based on chocolate and moringa oleífera powder in the canton Samborondón province of Guayas. - Villavicencio Párraga, Mirian Alexandra; Tumbaco Reyes, Luis Enrique; Arteaga Peñafiel, Marina Urbeci (Ingeniería Química y Desarrollo, 2024)
Gastronomy in the world has been evolving over time, every year there is a great variety and Delicious dishes that can be tasted in any corner of the country, gastronomy has made progress and that is how there are cities where you can enjoy its diversities as well as its culture, its traditions and its typical foods: the coastal region specifically in the Samborondón canton is where we will put into practice our research on the Moringa Oleífera, which is a shrub with innumerable nutritional properties, it is considered done of the foods that contribute to the well-being of human beings thanks to their variety of nutrients and benefits that they contribute to the body, we will use it as a proposal for the responsable application in a pastry product that, combined with cocoa, is an excellent proposal for its dissemination since it is produced only in 14 countries of the world.